How Safe Are Biological Agents in Pediatric Rheumatology? - Emine Nur Sunar Yayla; Çisem Yıldız; Pelin Esmeray Şenol; Nihal Karaçayır; Deniz Gezgin Yıldırım; Sevcan A. Bakkaloğlu (AVES Yayincilik, 2024)
Objective: Biologic therapy has changed the prognosis of patients with rheumatologic disease. Despite all benefits of the biological agents, adverse events may occur due to their long-term use. The aim of this study is to analyze the adverse events observed in pediatric patients who received biological treatment. Materials and Methods: This retrospective observational cohort study was conducted between January 2010 and January 2022. File records of 139 patients used biological agents for rheumatologic diseases in a pediatric rheumatology clinic were evaluated. Diagnosis, received treatment, the rationale for stopping treatment, requirement of tuberculosis prophylaxis, presence of an adverse event, and results were recorded. Results: The most used biological therapy was etanercept (41.7%). Anakinra, adalimumab, canakinumab were used in 30.9%, 27.3%, 23.7% of patients, and the others in less than 10%. Totally 491 adverse events (97.9/100 patient-years) were encountered during the duration of biological treatment. The most often adverse event was recurrent upper respiratory tract infection in the patients (31.9/100 patient-years). Elevated aminotransferase levels (10.4/100 patient-years), abdominal pain (7/100 patient-years), and headache (5.2/100 patient-years) were among the other common side effects. Isoniazid (INH) prophylaxis was needed before biological treatment in 20.9% of the patients. Tuberculosis developed in none of the patients followed-up for latent tuberculosis, however, it developed in a patient while receiving etanercept due to noncompliance with his scheduled outpatient visits during etanercept treatment. Conclusion: The most commonly used biological treatments were TNFi and IL-antagonists, and the majority of side effects were infections and laboratory abnormalities. Although the rate of serious adverse events is quite low, close follow-up of patients receiving biological therapy is very important.